Uniting of one-dimensional optimal filtering outcomes for semicausal and noncausal processing of Gaussian uniform images (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
Linear algorithms of uniting of one-dimensional optimal filtering outcomes for semicausal and noncausal processing of Gaussian uniform images are synthesized. Designed algorithms are implemented in two stages. At the first stage the one-dimensional Kalman filtering of Gaussian uniform image observations along each of considered coordinates is executed. At the second stage uniting of computed at the first stage estimations is executed. Analysis of designed algorithms is done on the model example by means of statistical modeling on computer. Comparing of designed algorithm with known algorithms is carried out. Characteristics of accuracy of estimations computed by designed algorithms by means of semicausal and noncausal processing of Gaussian uniform images are shown.